Analisis Konstitusional Otonomi Daerah dalam Pengelolaan Sumber Daya Air Berkelanjutan: Studi Kasus Sungai Citarum - Yashinta Irrina Mariana; Wahyu Donri Tinanbunan; Yopi Gunawan; Tri Setiadi (University of Muhammadiyah Malang, 2026)
This study examines the constitutional framework of regional autonomy in sustainable water resource management, with the Citarum River as the case study. The research focuses on the distribution of authority among the central government, provincial government, and regency or municipal governments in controlling pollution, protecting river ecosystems, and coordinating water governance. This study uses a normative-empirical legal approach based on document analysis of constitutional norms, statutory regulations, policy documents, official reports, and relevant academic literature. The findings show that the Citarum River is governed through a strong constitutional mandate under Article 33 paragraph (3) of the 1945 Constitution, yet its implementation still faces overlapping authority, sectoral coordination gaps, uneven local capacity, and weak continuity of law enforcement. The study concludes that sustainable Citarum management requires clearer authority mapping, stronger provincial coordination, consistent enforcement, community participation, and policy harmonization between national strategic programs and regional autonomy.